2022
DOI: 10.3389/fpsyt.2022.848709
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Functional Neuroimaging, Monoamine Neurotransmitters, and Behavioral Score on Depressive Tendency in Intensive Care Unit Medical Staffs Induced by Sleep Deprivation After Night Shift Work

Abstract: BackgroundIntensive care unit (ICU) medical staffs undergoing sleep deprivation with perennial night shift work were usually at high risk of depression. However, shift work on depression-related resting-state functional magnetic resonance imaging was still not fully understood. The objective of this study was to explore the effects of sleep deprivation in ICU medical staffs after one night of shift work on brain functional connectivity density (FCD) and Hamilton Depression Rating Scale (HAMD) scores. Also, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Psychological analyses have made a lot of progress in emotional studies, and these pioneering works have helped locate many important structures involved in basic emotions. However, the characteristic feature of monoamine neurotransmitters is their broad projection, which can affect the function of the whole brain and even the whole body [ 151 ]. Thus, monoamine neurotransmitters are also called neuromodulators, including dopamine, norepinephrine, and serotonin (DA, NE, and 5-HT).…”
Section: Monoamine Neurotransmitter and Other Neurotransmittersmentioning
confidence: 99%
“…Psychological analyses have made a lot of progress in emotional studies, and these pioneering works have helped locate many important structures involved in basic emotions. However, the characteristic feature of monoamine neurotransmitters is their broad projection, which can affect the function of the whole brain and even the whole body [ 151 ]. Thus, monoamine neurotransmitters are also called neuromodulators, including dopamine, norepinephrine, and serotonin (DA, NE, and 5-HT).…”
Section: Monoamine Neurotransmitter and Other Neurotransmittersmentioning
confidence: 99%
“…Increasing lines of evidence indicate that monoamine neurotransmitters play a significant role in the regulation of SD and memory function in the brain [ 9 , 150 , 151 ]. SD contributes to the decline of memory, as a study demonstrated that the serum NA level of medical staff as subjects decreased significantly [ 152 ]. Following different SD times (96, 120, 144 h), Wistar rats showed changes in monoamine neurotransmitters in the hypothalamus, with decreases in NA and DA and increases in 5-HT and 5-HIAA [ 153 ].…”
Section: Potentially Relevant Mechanismsmentioning
confidence: 99%
“…73 In an acute sleep deprivation experiment on a healthy population, similar to animal experiments, serum 5-HT levels were elevated in subjects and metabolites of 5-HT were shown to have a possible role in antidepressants. 74 5-HT is widely distributed in the peripheral and central nervous system. The most characteristic central system analgesic pathways are the 5-hydroxytryptaminergic-norepinephrinergic pathway and the opioidergic pathway.…”
Section: -Hydroxytryp-taminementioning
confidence: 99%
“… 73 In an acute sleep deprivation experiment on a healthy population, similar to animal experiments, serum 5-HT levels were elevated in subjects and metabolites of 5-HT were shown to have a possible role in antidepressants. 74 …”
Section: The Underlying Mechanisms Of Sleep Deprivation Exacerbating ...mentioning
confidence: 99%